Persilangan Ikan Nila (Oreochromis niloticus) Dari Berbagai Varietas Serta Ikan Mujahir (Oreochromis mossambicus) Untuk Mendapatkan Benih Bersifat Unggul - Aulia, Rahma; Permana, Dian; Naryaningsih, Agustien; Soleh, Mohamad; Siswanto, Siswanto; Sahlan, Sahlan (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research aims to produce seeds from the crossbreeding of nile tilapia (Oreochromis niloticus) of the jabir, nirwana, and sultana strains, as well as Mozambique tilapia (Oreochromis mossambicus). The crosses involved using male jabir nile tilapia with female nirwana nile tilapia and male mozambique tilapia with female sultana nile tilapia. The breeding was conducted in a 1:3 ratio of male to female. The spawning process occurred over a 16-day cycle, followed by a 28-day period of larval rearing. Crossbreeding between jabir and nirwana resulted in a higher spawning rate (17%) compared to the crossbreeding of mozambique and sultana (7%). The specific growth rate of seeds from the jabir and nirwana cross (14%) was not significantly different from the mozambique and sultana cross (13%). The survival rate of seeds from the jabir and nirwana cross (80%) was higher than from the mozambique and sultana cross (70%). Crossbreeding between male jabir nile tilapia and female nirwana nile tilapia exhibited better performance compared to the crossbreeding of male mozambique tilapia and female sultana nile tilapia.